Steinbeck and the Environment : Interdisciplinary Approaches - Steinbeck, Elaine A.; Tiffney, Wesley N.; Shillinglaw, Susan; Beegel, Susan F., 1954- (Book collections on Project MUSE., 1997)
John Steinbeck, intellectual soulmate of pioneering ecologist Edward F. Ricketts, developed a literary vision unique for its biological holism. From his exploration of the environmental disaster in the Dust Bowl region described in The Grapes of Wrath to his voyage of scientific and spiritual discovery among near-pristine marine ecosystems recounted in Log from the Sea of Cortez, Steinbeck's entire canon probes the multiple and interlocked dimensions of his outstanding theme - that human beings and their environment are an inseparable unit. Written by scholars from various disciplines - marine biology, the social and physical sciences, environmental studies, feminist theory, history, and philosophy, as well as American literature - these essays offer a dynamic contribution to the study of Steinbeck by considering his writings from an environmental perspective. And although these writers come from different backgrounds, they find a common theme - Steinbeck blended his literary vision with a unique understanding and appreciation of the environment.